Zerumbone improved immunoreactivity of neuropeptides in monosodium iodoacetate induced knee osteoarthritis in rat - Al-Saffar, Fayak Jabbar Taqi; Ganabadi, Shanthi; Fakurazi, Sharida; Yaakub, Halimatun (Academic Journals, 2011)
The main objective of this investigation was to explore the improvement effect of oral administration of zerumbone on the density of protein gene product; calcitonin gene related peptide and neuropeptide Y immunoreactive nerve fibers against monosodium iodoacetate induced osteoarthritis changes in rat's knee synovial membrane. Prostaglandin (PG) E2 and F2α were determined to assess their role during osteoarthritis events and post zerumbone application. Forty rats were divided equally into four groups. Rats in the first and second groups were treated with two different concentrations of zerumbone. Rats in the third group received celecoxib (Celebrex®) and served as positive control; whereas those of the fourth group were given corn oil and served as the negative control. The results revealed lower pathology score beside an improvement of the immunoreactive nerve fibers densities in zerumbone treated groups compared with the negative control. Different prostaglandin levels were detected within the different treated groups. The data showed that, zerumbone had dose dependent plausible improvement effect against the depleted immunoreactive nerve fibers which occurred after monosodium iodoacetate injection. The prostaglandin E2 but not PGF2α showed distinct role during the osteoarthritis events and the post oral treatment with zerumbone.